Cases and Efforts to Escape from the Soviet Union by Lithuanians - Fabijonavičiūtė, Agnė (Genocidas ir rezistencija, 2001)
The work depicts the efforts of Lithuanians to escape from the Soviet Union during the 1970s. Just in 1970 there were three attempts to run away from the USSR. That year the father and the son Brazinskai hijacked a plane and managed to escape to Turkey. During the incident the crewmembers were injured, and the stewardess was killed. After 6 years of trials in Turkey, Brazinskai emigrated to the USA. The KGB initiated the case called “Piratai” (“Pi rates”), seeking to get them back to the Soviet Union. The case of Brazinskai was used for ideological struggle with the West. Another case, investigated in the work, is the defection of Lithuanian sailor S. Kudirka during official meeting near the USA coast. However, he was returned to the Soviets, and sent to prison for ten long years. After six years S. Kudirka was released and emigrated with his family to the USA. J. Simokaitis and his wife G. Mickutė also tried to hijack a plane and escape to Sweden, but were arrested and sent to prison. J. Simokaitis was sentenced to death, but later the sentence was changed to 15 years imprisonment. The last case investigated in the work is the escape of A. Sakauskas to Sweden. A. Sakauskas succeeded and lives now in Sweden. All these cases demonstrated to the world the problems existing in Lithuania, disclosed the attempts of Soviet propaganda to present life in the SSRS as devoid of hardships. The research is supplemented with the material from the KGB archive.